Design and Fabrication of a Modular Mini-Hydro Turbine for Off-Grid Electrification in Nigeria’s Riverine Communities - Hyginus Unegbu; Danjuma YAWAS (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
This research presents the design, simulation, fabrication, and performance evaluation of a modular crossflow mini-hydro turbine engineered to address persistent energy access challenges in Nigeria’s off-grid riverine communities. The system was conceived to operate efficiently under low-head, variable-flow conditions typical of inland watercourses, using a fully modular design framework that emphasises ease of deployment, maintenance, and scalability. Computational fluid dynamics (CFD) was employed during the design phase to optimise internal flow characteristics, nozzle geometry, and runner-blade profiles. The turbine achieved a hydraulic efficiency of 62% to 68% and produced a consistent power output of 300–340 W per module across a range of flow conditions. Empirical testing validated the CFD predictions with deviations remaining under 7%, confirming the design’s reliability. Environmental assessments revealed noise and vibration levels well within rural acceptability thresholds, and casing integrity was preserved under continuous operational testing. A key innovation of the system lies in its modular configuration. All primary components—including the shaft-runner assembly, generator unit, and control interface—were designed to be independently replaceable using basic tools. Scalability tests confirmed that dual-module operation retained 92% efficiency, demonstrating the viability of phased expansion in community-scale installations. The turbine aligns with national electrification objectives and offers a replicable, context-sensitive solution for rural electrification in sub-Saharan Africa. The study contributes a practical and scalable model for clean energy deployment, advancing the case for modular micro-hydro systems as critical infrastructure in remote and underserved regions.